The issues of the Arabian Peninsula in the debates of the Iraqi Parliament (19581950) (Journal of the College of Basic Education, 2023)
Saudi Arabia and Yemen were mentioned in the discussions of the lower house of the Iraqi parliament.Those who were deliberating on Iraq's foreign policy in the Arab and international arenas.The sessions gave good opinions that expressed what was going on among the Iraqi public opinion regarding the desire to developThe relationship with the Kingdom of Saudi Arabia, and the repeated British attacks on Yemen.It aims at undermining her independence, and these are deep feelings that we rarely find, and they are rooted in the hearts ofThe Iraqis who are eager to extend aid and help to their Arab brothers in all their countries, as well asDesire and keenness to strengthen their relations with those countries, in order to achieve an Arab unanimity and influenceGlobally, towards Arab and international issues, and in international forums.The Iraqi representatives expressed, through their arguments that they expressed during these discussions,which specialized in reviewing the internal and external policy of successive Iraqi governments.of them as far as the topic of foreign policy is concerned, when they denounce the continuation of the attacksBritain against brotherly Yemen, demanding the Arab countries individually or collectively through the universityArabia, to take appropriate measures to protect the Yemeni people who are defending their country, which is supposed to beTo fulfill its lofty mission, which is hoped to be done, to support the Arab liberation movements, and to provideSupport for our brothers in Yemen. In addition to that, official and popular Iraqi contacts have continued.Yemeni and both of them refer to the importance of taking a unified position on the issues of the Arab nation.The Iraqi Parliament, telegrams of denunciation to brotherly countries, Islamic and foreign countries, aboutThe French aggression on Marrakesh, Yemen was among those countries that supported the position of the generalIraqis expressed through their representatives in the House of Representatives, expressing their willingness to take stepsIt would assist the Marakish people in their struggle to gain the independence of their country, as well as the practice of variousThe available pressures on France to push it to change its hostile policy and to stop its aggression.